Students’ ability in Analyzing Passive Voice in Explanation and Report Texts at Second Year of SMAN 1 Padang Bolak - Siregar, Sarwan; Fitrawati, Fitrawati (Universitas Negeri Padang, 2024)
This study was aimed to describe students’ abilty in anlyzing passive voice in Explanation and Report Texts at second year of SMAN 1 Padang Bolak. The research design was quantitative descriptive. The population of this research was the second grade students of SMAN 1 Padang Bolak. The population was 120 students from four classes ; XI MIA I, XI MIA II, XI MIS I, XI MIS II. The sample was taken by simple random sampling technique so that the number of sample obtained was 30 students. The instrument that was used in this research was grammar test consisted 40 questions. The first 15 questions was in the form of analysis and the rest question was in the form of short answer. The finding of the research reveals that students’ ability in analyzing passive voice in Explanation and Report Text at second year of SMAN 1 Padang Bolak was in poor classification with avarage score 35.73. The research also reveals some most difficulties that were faced by students in analyzing passive voice in Explanation and Report texts. These difficulties were changing active voice into passive voice, determining and arranging the subject and the object (agent or doer) in the passive voice, changing infinitive verb into verb 3 (past Participle), changing modal auxiliary verb into passive voice form.